Karakter dan Akhlak Pemimpin dalam Perspektif Islam - Siti Fatimah Siregar; Yudistira Fuady; Muhammad Fadli; Afif Al-Bukhori; Putri Nurhayati Lubis; Saidatun Nisa Nasution; Riki Wahyudi; Suryadi Matanari; Muhammad Junaidi; Ira Suryani (Mahesa Research Center, 2018)
This article discusses the importance of character and moral factors in leadership from the perspective of Islam. Ideal leadership is related to the progress of a civilization and a nation. Islam and its followers want a leader who has good character and noble character. The source of the reference to being a leader for Muslims comes from the Koran and Hadith, imitating the personality of the Prophet Muhammad and the Khulafaur Rashidin. In the context of the state, the reference is also based on the rules and regulations of the law that inacted in Indonesia